Visual Preaching in The AI Era: Optimizing Graphic Design for a More Effective Islamic Message - Ilham, Ilham; Sitompul, Nurul Adha; Hasibuan, Putri; Ulandari, Ulandari; Siregar, Anggi Aulia (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The development of artificial intelligence (AI) technology has had a significant influence on the graphic design production process, including in conveying Islamic messages through visual media.This research aims to explain how AI can be optimized to increase the effectiveness of visual da'wah without neglecting Islamic aesthetic and ethical values.Using a descriptive qualitative approach, this study examines the use of AI as a tool capable of accelerating the creative process, improving visual quality, and enabling the personalization of Islamic preaching messages according to the characteristics of the audience.The research results show that AI can function as a supporter that strengthens the delivery of Islamic messages, as long as its use remains supervised by designers to ensure it is in line with the principles of da'wah and does not cause distortion of meaning.The balanced optimization of technology and human creativity is the key to the success of relevant, communicative, and effective visual preaching in the digital era.